Comparison of colorimetric and electrochemical (Easy Touch GCU Meter) methods for determination of blood uric acid in clinical practice in patients with gout and hyperuricemia (data from a pilot study) - M. S. Eliseev; E. V. Panina; O. V. Zheliabina (Современная ревматология, 2023)
Hyperuricemia (HU) is a condition caused by an increase in serum uric acid (UA) levels above 360 μmol/l. Often HU is asymptomatic, but under the influence of genetic and environmental factors, attacks of peripheral arthritis (gout) may occur. Remission of gout is achieved by normalization of UA serum levels, which can be determined by a colorimetric or electrochemical method, although the latter is not currently commonly used in clinical practice to control UA levels.   Objective: to compare the standard colorimetric and electrochemical methods (Easy Touch GCU Meter) for monitoring UA levels.   Material and methods. 30 gout patients were included in the study. This group included subjects with current/anamnestic asymptomatic HU andpatients with a confirmed diagnosis of gout (ACR/EULAR 2015 criteria). The examination included a general examination, history taking, and laboratory testing. The determination of UA level by the colorimetric method in venous blood serum was performed no later than 5 minutes after collection, and the determination of UA level in fresh whole capillary blood from the fingertip by the electrochemical method (Easy Touch GCU Meter) – immediately after collection.   Results and discussion. The average values of UA blood level determined by the two compared methods differed by 13.9 μmol/l (3.9 % with respect to the colorimetric method). The high value of the correlation coefficient (r = 0.86) indicates a close linear relationship between the compared results and their good agreement. The method is also applicable in patients with achieved normouricemia.   Conclusions. The method of electrochemical determination of UA level in subjects with HU and gout can be used in real clinical practice for self-monitoring.